PEMBUATAN FEEDS INSTAGRAM MENGGUNAKAN CANVA PRO SEBAGAI MEDIA PROMOSI PADA S.1824 PT. NATURAL NUSANTARA (STOCKIST LAMONGAN) - Safitri, Arnadya Amira; Maskur, Maskur; Utomo, Heru (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
Stockist S.1824, a business unit of PT Natural Nusantara (Nasa Distributor), offers various services and products, including agrocomplex, biological control, homecare, health, cosmetic, and body care items. Although promotions are conducted through several channels, including Instagram, the platform's effectiveness is limited due to insufficient product information and unattractive designs. This study aims to evaluate the effectiveness of Instagram feeds as a promotional tool by redesigning feeds using Canva Pro. The research employs action research methodology, encompassing planning, action, observation, and reflection. Data were collected through questionnaires distributed to the business owner, employees, marketing experts, IT experts, and potential customers. The effectiveness of the feed designs was assessed using the EPIC Model (Empathy, Persuasion, Impact, Communication). The study, conducted in two cycles, found that the new feed designs were highly effective as a promotional tool. Respondents agreed that the redesigned feeds significantly improved the promotional impact for Stockist S.1824.